Thermogravimetric Analysis of Indonesian Low-Rank Coal: Optimization of Drying Temperature and Kinetic Modeling - Haq, Shofa Rijalul; Shafiyurrhaman, Muhammad Faiz; Kurniawan, Ade; Prasetyo, Yuda; Prasetyo, Imam; Jeon, Sanghee (Jurnal Rekayasa Proses, 2025)
Drying high-moisture of low rank coal in the mining sector is essential for increasing energy efficiency and ensuring stability in its use as an energy source. This study aims to determine the optimal drying temperature and kinetic parameters for Indonesian low rank coal (i.e., lignite and sub-bituminous) using thermogravimetric analysis (TGA) under both isothermal and non-isothermal conditions. Coal samples were tested at three heating rates (5, 10, and 20°C/min) and three fixed temperatures (150, 200, and 250°C). Several drying kinetics models, including the Newton, Henderson and Pabis, Logarithmic, and Page models, were used to evaluate the drying characteristics of both coal types. The results indicate that the Page model provided the best fit, with the highest ?2 value and the lowest ?2 value, making it the most accurate model for describing coal drying rates under various conditions. The optimal drying temperature for lignite was 83.04°C, with an activation energy of 3224.04 J/mol, while for sub-bituminous coal, the optimal temperature was 109.65°C with an activation energy of 17972.83 J/mol. These findings support the optimization of the drying process in the industry, particularly for efficiently reducing coal moisture content without compromising energy quality.